2016
DOI: 10.1242/jeb.146209
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intermittent hypoxia on oxidative stress and protein degradation in molluscan mitochondria

Abstract: Oxygen fluctuations represent a common stressor in estuarine and intertidal environments and can compromise the mitochondrial integrity and function in marine organisms. We assessed the role of mitochondrial protection mechanisms (ATP-dependent and -independent mitochondrial proteases, and antioxidants) in tolerance to intermittent hypoxia or anoxia in three species of marine bivalves: hypoxia-tolerant hard clams (Mercenaria mercenaria) and oysters (Crassostrea virginica), and a hypoxia-sensitive subtidal scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 47 publications
0
25
0
Order By: Relevance
“…In accordance to our results, Rivera-Ingraham et al (2013) demonstrated that mussels M. edulis presented unaltered protein carbonyl content after reoxygenation, followed by a burst of LPO in same condition. Furthermore, Ivanina and Sokolova (2016) also observed no differences in carbonyl levels in Mercenaria mercenaria clams exposed to anoxia or hypoxia followed by reoxygenation. Thus, the present findings indicate that air exposure during ebb tide did not produce enough stress to generate protein oxidation in mussels.…”
Section: Accepted Manuscriptmentioning
confidence: 76%
“…In accordance to our results, Rivera-Ingraham et al (2013) demonstrated that mussels M. edulis presented unaltered protein carbonyl content after reoxygenation, followed by a burst of LPO in same condition. Furthermore, Ivanina and Sokolova (2016) also observed no differences in carbonyl levels in Mercenaria mercenaria clams exposed to anoxia or hypoxia followed by reoxygenation. Thus, the present findings indicate that air exposure during ebb tide did not produce enough stress to generate protein oxidation in mussels.…”
Section: Accepted Manuscriptmentioning
confidence: 76%
“…In more pronounced hypercapnic and aragonite undersaturated conditions, C. virginica upregulates antioxidant proteins (14 days; ~3500 µatm and 7.5 pH; Tomanek et al, 2011) and a similar response is also seen in the Yesso scallop Patinopecten yessoensis (duration = 14 days; ~2200 µatm, 7.5 pH, and 0.7 Ω; Liao et al, 2019) and mussel Mytilus coruscus (duration = 45 days; ~2800 µatm, 7.3 pH, and 0.5 Ω; Huang et al, 2018). Alternatively, a seemingly 'preparatory' energetic cost of antioxidant synthesis is found in a variety of taxa (Hermes-Lima and Zenteno-Savıń, 2002;Ivanina and Sokolova, 2016) and suggests adaptive energy reallocation to scavenge ROS formed by aerobic recovery when a stressor is lifted.…”
Section: Oxidative Status and Repeated Stress Encountersmentioning
confidence: 67%
“…Adaptive cellular defense against oxidative damage is thought to have an important evolutionary role in the longevity of the ocean quahog Arctica islandica (lifespan > 400 years) due to a lifestyle of metabolic dormancy (when burrowed) and aerobic recovery (Abele et al, 2008). Further, Ivanina and Sokolova (Ivanina and Sokolova, 2016) found hypoxia-tolerant marine bivalves show anticipatory and compensatory upregulation of antioxidant proteins to mitigate oxidative bursts under hypoxiareoxygenation. Such adaptive responses have yet to be explored under hypercapnic conditions to identify species tolerant to OA stress.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these caveats that come with using MitoB to detect mitochondrial H 2 O 2 , the lack of a direct connection between ROS generation and presumed downstream effects of ROS is not unique to this study and has been observed in other organisms. For example, in molluscs exposed to anoxia+recovery and hypoxia+recovery, changes in aconitase activity (the inhibition of which is directly related to the presence of superoxide) did not mirror changes in total antioxidant capacity nor measures of oxidative damage (Ivanina and Sokolova, 2016). These results illustrate the importance of taking a multifaceted approach to understanding ROS metabolism since measuring only one aspect, e.g.…”
Section: Discussionmentioning
confidence: 90%
“…In contrast, much less is known about whether animals that inhabit these environments have also evolved strategies to minimize ROS production or mitigate the damaging effects of ROS. Several studies support the idea that hypoxia tolerance is associated with lowered mitochondrial ROS generation (shown in elasmobranchs, mollusks and hypoxia-acclimated killifish Fundulus heterolitus; Du et al, 2016;Hickey et al, 2012;Ivanina and Sokolova, 2016), whereas there does not appear to be a consistent link between hypoxia tolerance and antioxidant defenses in fish (Leveelahti et al, 2014). However, a previous in vitro study of brain mitochondria from multiple species of intertidal sculpin (Cottidae, Actinopterygii) showed that mitochondria from more hypoxia-tolerant species emitted more H 2 O 2 per O 2 molecule consumed under oligomycin-induced state IV conditions compared with a less hypoxia-tolerant species, and H 2 O 2 emitted per mg mitochondrial protein measured did not differ (Lau and Richards, 2019).…”
Section: Introductionmentioning
confidence: 76%